The antecedents of trust and relational commitment - Marques, Alzira; Coelho, Arnaldo (Review of Business Management, 2007)
In the relationship marketing field, especially on the buyer-seller relationship, the commitment has been object of an impressive body of literature, on both conceptual and empirical way. However, most of it is focused on customer behavior and little attention has been given to the seller perspective about trust and commitment. Based on a sample of 192 private Portuguese companies, this study aims to show the impact of trust and relational value on commitment, evaluated in terms of continuity of the relation. Results show that only trust has a direct effect on commitment, explaining 31,5% of its variance. Relational value explains 19,4% of the variance of trust in the customers’ integrity and reliability , so it can influence commitment in an indirect way. Key-words: Relationship marketing. Commitment. Trust. Relational value.